GOOD CORPORATE GOVERNANCE ON CARBON EMISSION DISCLOSURE AND COMPANY PERFORMANCE - Maryanti , Eny; Jannah , Etikakhul (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Climate change and carbon emissions have become pressing global concerns, requiring companies to adopt transparent carbon emission disclosure practices. Specific Background: In Indonesia, the impact of such disclosures on corporate financial performance, particularly in the manufacturing sector, is of growing interest. Corporate governance mechanisms, such as institutional ownership, independent boards of commissioners, and nationality diversity, may influence carbon emission disclosure practices. Knowledge Gap: Limited research has explored the combined influence of these governance variables on both carbon emissions disclosure and financial performance in Indonesia's food and beverage manufacturing sector. Aims: This study aims to analyze the effects of institutional ownership, independent boards of commissioners, and nationality diversity on carbon emissions disclosure and financial performance. Results: The results show that while institutional ownership has no significant effect on carbon emission disclosure or financial performance, both independent boards of commissioners and nationality diversity have a positive influence on carbon emission disclosure. Additionally, independent boards positively affect financial performance, while nationality diversity does not. Novelty: This study highlights the pivotal role of board independence and nationality diversity in promoting environmental transparency, revealing that institutional ownership does not play as crucial a role as expected in either carbon emission disclosure or financial performance. Implications: The findings suggest that enhancing board diversity and independence may improve corporate environmental practices, but more strategic oversight is needed to translate these practices into financial performance improvements.